Analisis Penerapan P5 Terintegrasi TRI-N dan TRI-Nga untuk Meningkatkan Dimensi Gotong Royong pada Siswa SD - Qomariah Binti Zulaihah; Fenindita Yunika Ningrum; Daryanti Apriani; Banun Havifah Cahyo Khosiyono; Berliana Henu Cahyani; Ana Fitrotun Nisa (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The law attitudes of mutual cooperation in grade VI C students of Bhayangkara State Elementary School is a concern for teachers, this study aims to analyze the effectiveness of the implementation of P5 integrated with TRI-N and TRI-Nga in improving the dimension of mutual cooperation in elementary school students. The research uses a qualitative descriptive approach with data collection methods using interviews, observations, and documentation. The results obtained are that the implementation of P5 in grade VI C Bhayangkara State Elementary School which is integrated with Tri – N and Tri-Nga is able to increase the dimension of mutual cooperation in students, in addition to the results of interviews conducted with students show that students feel more able to enjoy the learning process with friends in P5, besides that it was revealed that students feel happy when they are able to help friends who are in difficulty, and be able to understand the concept of mutual cooperation by connecting the concept with his personal experience in daily life, So that during discussion activities students can show a mutual cooperation attitude.